THE IMPLEMENTATION OF INDIA’S INTEGRATED CHILD DEVELOPMENT SCHEME: ANALYSIS & ANGANWADI PERFORMANCE - Chauhan, Versha; Sinha, Sandhya; Singh, Arvind Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
After thirty years of sustained operation, the Integrated Child Development Services (ICDS) program continues to be the most distinctive early childhood development initiative globally. The program’s package of services encompasses supplementary nutrition, immunisations, health checkups, and referral services for children under six, as well as for expectant and nursing mothers. Children between the ages of three and six undergo non-formal preschool education, whilst women aged fifteen to forty-five participate in health and nutrition education. The initiative prioritises on the needs of the most vulnerable children under three by improving carers’ capacity to provide engaging activities and superior early childhood care. This study evaluates the successful performance of the ICDS within our sociocultural framework over recent years, focussing on ensuring children’s rights to survival, growth, protection, and development, as well as their active participation in their surrounding environment. This study will analyse the function of Anganwadis in Lucknow, as per the ICDS program, in enhancing the health and nutritional condition of children in rural regions, with an emphasis on evaluating their performance concerning funding from five-year plans. This study will conclude with an assessment of the project’s implementation success aimed at achieving universal health and education in the rural districts of Uttar Pradesh for developmental purposes. It additionally provides recommendations for the execution of the ICDS and the performance of Anganwadis. The project will be executed successfully and efficiently with the assistance of the government, semi-government entities, and other stakeholders to achieve the Government of India’s Millennium Development Goals. This study will be descriptive and will mostly utilise secondary data obtained from government statistics, official websites, journals, magazines, and other sources.